2019
DOI: 10.1523/jneurosci.2630-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Innervation onto Striatal Neurons Potentiates GABAergic Synaptic Output

Abstract: Striatal output pathways are known to play a crucial role in the control of movement. One possible component for shaping the synaptic output of striatal neuron is the glutamatergic input that originates from cortex and thalamus. Although reports focusing on quantifying glutamatergic-induced morphological changes in striatum exist, the role of glutamatergic input in regulating striatal function remains poorly understood. Using primary neurons from newborn mice of either sex in a reduced two-neuron microcircuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…In agreement with this, we have previously shown that reactive oxygen species enhance recruitment of postsynaptic a6but not a1-containing GABA A Rs in mouse granule cells (Accardi et al, 2015), whereas others have shown a presynaptic action of NO on GABA release from rat Golgi cells (Mapelli et al, 2016). Differential regulation of input-specific GABAergic synapses onto the same neuron has recently been described in the cerebral cortex (Chiu et al, 2018) and striatum (Paraskevopoulou et al, 2019), consequently, it is possible that a similar arrangement is found in both inhibitory synapses of MLIs and granule cells of the cerebellum. An important caveat to both presynaptic and postsynaptic roles of NO in granule cells, however, is that nNOS expression in the presynaptic terminals of Golgi cells is high in the rat but almost completely absent from the mouse, particularly mice with the C57BL/6 background used in this study (Kaplan et al, 2013).…”
Section: No Strengthens Inhibitory Gabaergic Synapses Following Nmdarsupporting
confidence: 74%
“…In agreement with this, we have previously shown that reactive oxygen species enhance recruitment of postsynaptic a6but not a1-containing GABA A Rs in mouse granule cells (Accardi et al, 2015), whereas others have shown a presynaptic action of NO on GABA release from rat Golgi cells (Mapelli et al, 2016). Differential regulation of input-specific GABAergic synapses onto the same neuron has recently been described in the cerebral cortex (Chiu et al, 2018) and striatum (Paraskevopoulou et al, 2019), consequently, it is possible that a similar arrangement is found in both inhibitory synapses of MLIs and granule cells of the cerebellum. An important caveat to both presynaptic and postsynaptic roles of NO in granule cells, however, is that nNOS expression in the presynaptic terminals of Golgi cells is high in the rat but almost completely absent from the mouse, particularly mice with the C57BL/6 background used in this study (Kaplan et al, 2013).…”
Section: No Strengthens Inhibitory Gabaergic Synapses Following Nmdarsupporting
confidence: 74%
“…Other work has explored the competition between glutamatergic and GABAergic neurons when grown as mixed or homotypic pairs (Rao et al, 2000;Chang et al, 2014;Wierda and SĂžrensen, 2014), or between wildtype and mutant neurons that lack presynaptic proteins involved in transmitter release (Tarsa and Goda, 2002;GarcĂ­a-PĂ©rez et al, 2015). Finally, two-cell microislands with different combinations of striatal, cortical and thalamic neurons have been used to examine the effect of glutamatergic input on refining striatal output (Paraskevopoulou et al, 2019).…”
Section: A Defined Neighborhoodmentioning
confidence: 99%
“…Inhibitory output has also been shown to be modulated by activity, through modulation of rate limiting enzymes of GABA synthesis (Lau & Murthy 2012) or GABA transporters (De Gois et al 2005). Such plasticity mechanisms have also recently been reported in the chandelier cells (Pan-Vazquez et al 2020) and striatial inhibitory neurons (Paraskevopoulou et al 2019) during development. Altogether, these studies indicate that our model of tonic inhibition modulated as a function of synaptic input to the inhibitory neurons is a biologically plausible mechanism.…”
Section: Discussionmentioning
confidence: 79%